2016
DOI: 10.1007/s11738-016-2309-1
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and sucrose metabolism in leaves of Arabidopsis thaliana aos, ein4 and rcd1 mutants as affected by wounding

Abstract: We have investigated the influence of mechanical wounding of Arabidopsis rosette leaves on photochemical activity of photosystem II, gas exchange, sugar content and sucrose metabolism in wild-type plants and mutants impaired in hormonal balance. The aos (jasmonate deficiency), rcd1 (reduced sensitivity to ABA, ethylene, and methyl-jasmonate), and ein4 (ethylene insensitivity) mutants have been used. Generally, mechanical injury led to dynamic changes in metabolism, especially in sugar and carotenoid contents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…For the metabolic response to the agroinfiltration, two aspects have to be taken into consideration. The first aspect is the mechanical damage to the leaf which leads to a local and systemic response of the plant (León et al 2001 ; Savatin et al 2014 ; Lukaszuk et al 2016 ; Chen et al 2018 ). The local response consists of cellular repair and establishing a physical barrier against pathogen penetration of the damaged and therefore more easily accessible leaf area.…”
Section: Discussionmentioning
confidence: 99%
“…For the metabolic response to the agroinfiltration, two aspects have to be taken into consideration. The first aspect is the mechanical damage to the leaf which leads to a local and systemic response of the plant (León et al 2001 ; Savatin et al 2014 ; Lukaszuk et al 2016 ; Chen et al 2018 ). The local response consists of cellular repair and establishing a physical barrier against pathogen penetration of the damaged and therefore more easily accessible leaf area.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene negatively affects CWI activity in cell suspensions of Chenopodium rubrum [ 96 ] and increased CWI activity is observed in Arabidopsis ein4 mutants [ 97 ], suggesting that ethylene suppresses CWI activity. Accordingly, the 1-MCP application in our work led to a drastic increase in CWI activity ( Figure 8 B).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the 1-MCP treatment enhanced VI activity at 0 DPI in all treatments, but had no effect on infected samples at 1 DPI ( Figure 7 C,D). These data suggest that ethylene plays a negative role in regulating both CWI and VI [ 97 ], but after pathogen perception this control mechanism seems to be uncoupled. It remains to be tested whether such uncoupling is due to the pathogens’ capacity to change soluble sugars availability, by direct uptake or by using dedicated effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Even it may be that the mowing induced the plant’s regeneration signal. Because mere mechanical damage can also induce changes in carbohydrate and hormone content ( Chandra et al, 2012 ; Lukaszuk et al, 2017 ). In Furthermore, mechanical damage changes the activities of sucrose hydrolysis-related enzymes ( Lukaszuk et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, under stress conditions, plants synthesize various monosaccharides and disaccharides, such as glucose, fructose, galactose, sucrose, and trehalose, which provide a protective environment enabling plant cells to face stress ( Pommerrenig et al, 2018 ). At the same time, the cutting for the forage wheat is also mechanical injury, which can induce changes in plant carbohydrate metabolism ( Lukaszuk et al, 2017 ). In addition, previous study showed that long-chain non-coding RNAs (lncRNAs) might participate in the carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%